Sebuah Analisis Determinan Kepatuhan Konsumsi Obat ARV (Anti Retroviral) Pada Odhiv Di Kabupaten Oki : Analisis Data Sekunder - Hesti Sariningrum; Rico Januar Sitorus; Najmah Najmah (Jurnal Pharmacopoeia, 2026)
Adherence to antiretroviral (ARV) therapy is a key factor in the success of HIV treatment to achieve viral suppression and prevent drug resistance. Various demographic and clinical factors are presumed to influence patients’ adherence levels. This study aimed to analyze the association between sex, population type, clinical stage, and history of loss to follow up (LFU) with ARV adherence in OKI District. This study employed an analytic observational design with a cross-sectional approach. A total of 37 respondents receiving ARV therapy were included in the study. Data were analyzed bivariately using the chi-square test to determine the association between independent variables and ARV adherence level, with a significance level of 0.05. The majority of respondents demonstrated adherence levels >95%. Bivariate analysis showed no significant association between sex (p=0.203), population type (p=0.205), clinical stage (p=0.611), and history of LFU (p=0.099) with ARV adherence (p>0.05).  Sex, population type, clinical stage, and history of LFU were not significantly associated with ARV adherence. However, retention in care remains an important aspect in maintaining treatment continuity. Strengthening counseling, routine monitoring, and comprehensive service approaches are necessary to sustain optimal adherence levels.